Simulating tip effects in vertical-axis wind turbines with the actuator line method. Issue 3 (1st May 2022) - Melani, PF; Balduzzi, F; Bianchini, A
Abstract: Simulation of the complex, unsteady aerodynamics characterizing Darrieus rotors requires computational tools with a fidelity higher than the ubiquitous Blade Element Momentum (BEM) theory. Among them, the Actuator Line Method (ALM) stands out in terms of accuracy and computational cost. This approach, however, still fails to resolve the vortex-like structures shed at the blade ends, overestimating turbine performance at the higher rotational speeds. Moving from this background, in this study a comprehensive investigation on the ALM's capability to simulate tip effects and their impact on rotor performance is carried out. To this end, the ALM tool developed by the authors in the ANSYS ® FLUENT ® environment (v. 20.2) and specifically tailored to the simulation of vertical-axis machines was employed. Both a steady finite wing and a fictitious one-blade Darrieus H-rotor, for which high-fidelity blade-resolved CFD data are available as benchmark, were considered as test cases. ALM simulations were first performed without any correction for different cell sizes and force projection radii, so that the limits of the original approach could be assessed. Then, two different sub-models were applied: the classical semi-empirical Glauert correction and a new methodology based on the Lifting Line Theory (LLT), which was recently proposed by Dağ and Sørensen (DS). The latter was here adapted to vertical-axis machines. Eventually, the blade spanwise load profiles coming from the three approaches were assessed and compared, proving the superior performance of the DS model.